2021
DOI: 10.1186/s13075-021-02419-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide association study identifies susceptibility genes for rheumatoid arthritis

Abstract: Objective To identify rheumatoid arthritis (RA)-associated susceptibility genes and pathways through integrating genome-wide association study (GWAS) and gene expression profile data. Methods A transcriptome-wide association study (TWAS) was conducted by the FUSION software for RA considering EBV-transformed lymphocytes (EL), transformed fibroblasts (TF), peripheral blood (NBL), and whole blood (YBL). GWAS summary data was driven from a large-scale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The imputed gene expression can then be used in place of genotypes to assess the effect of genes on a given phenotype (Gamazon et al, 2015). This strategy has been previously used to identify candidate genes associated with schizophrenia, attention deficit hyperactivity disorder and other complex traits (Gusev et al, 2018;Liao et al, 2019;Lindström et al, 2019;Wu et al, 2021). Here, we found that the predicted expression levels of EP300 in different metabolic-related tissues of patients with FEP receiving APs were significantly associated with increases in body weight, BMI, total cholesterol levels, LDL cholesterol levels and TG concentrations at the 6-months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The imputed gene expression can then be used in place of genotypes to assess the effect of genes on a given phenotype (Gamazon et al, 2015). This strategy has been previously used to identify candidate genes associated with schizophrenia, attention deficit hyperactivity disorder and other complex traits (Gusev et al, 2018;Liao et al, 2019;Lindström et al, 2019;Wu et al, 2021). Here, we found that the predicted expression levels of EP300 in different metabolic-related tissues of patients with FEP receiving APs were significantly associated with increases in body weight, BMI, total cholesterol levels, LDL cholesterol levels and TG concentrations at the 6-months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale GWAS summary data set of DCS was obtained from the published study [12]. In short, this summary data set contains 3739 diagnosed DCS and 382326 controls of European from the UK Biobank [12].…”
Section: Gwas Summary Datasets For Dcsmentioning
confidence: 99%
“…A large-scale GWAS summary data set of DCS was obtained from the published study [12]. In short, this summary data set contains 3739 diagnosed DCS and 382326 controls of European from the UK Biobank [12]. Information about various phenotypes has been collected from every participant, and blood samples were taken when the subjects visited a UK Biobank assessment center [12].…”
Section: Gwas Summary Datasets For Dcsmentioning
confidence: 99%
See 2 more Smart Citations